2004
DOI: 10.1074/jbc.m212839200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Conserved Casein Kinase Sites Regulates cAMP-response Element-binding Protein DNA Binding in Drosophila

Abstract: The Drosophila homolog of cAMP-response elementbinding protein (CREB), dCREB2, exists with serine 231, equivalent to mammalian serine 133, in a predominantly phosphorylated state. Thus, unlike the mammalian protein, the primary regulation of dCREB2 may occur at a different step from serine 231 phosphorylation. Although bacterially expressed dCREB2 bound cAMP-response element sites, protein from Drosophila extracts was unable to do so unless treated with phosphatase. Phosphorylation of recombinant protein by ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…In Drosophila, it has been shown that the KID domain of most dCREB2 proteins exists in a phosphorylated active state. As a result, in Drosophila, CREB activity has been postulated to be controlled at the level of DNA binding to its DNA elements [55]. Two putative CRE sites were identified close to 55b in the slo control region by sequence analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, it has been shown that the KID domain of most dCREB2 proteins exists in a phosphorylated active state. As a result, in Drosophila, CREB activity has been postulated to be controlled at the level of DNA binding to its DNA elements [55]. Two putative CRE sites were identified close to 55b in the slo control region by sequence analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to differences in the regulatory mechanisms controlling mammalian and fly CREBs. In contrast to mammalian CREB whose activity is mostly correlated with the phosphorylation level of Ser-133, a large portion of dCREB2 exists with Ser-231 in a phosphorylated state, suggesting that other mechanisms must be important in regulating its activity (38). Alternatively, polyQ in this fly model is overexpressed as a peptide, whereas other studies have used polyQ runs in the context of htt protein residues surrounding the expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-dCREB2 monoclonal and Ser-231 phosphospecific anti-pCREB rabbit polyclonal antibodies have been described (38).…”
mentioning
confidence: 99%
“…This might also apply to honeybee lLTM formation, which depends on the bees' feeding state (Friedrich et al 2004). Third, research in the fruit fly suggests that the rate limiting step for the D. melanogaster dCREB2 activity is not the phosphorylation of the S133 homologous serine residue but the nuclear entry and DNA binding of dCREB2, which is regulated by phosphorylation of residues other than the S133 homologous one (Horiuchi et al 2004). Moreover, the nuclear entry rate of pCREB2 correlates with memory formation (Fropf et al 2013).…”
Section: The Level Of Pamcreb Is Not Altered Directly After Classicalmentioning
confidence: 99%